Gratitude and Problem Behaviors in Adolescents: The Mediating Roles of Positive and Negative Coping Styles - Sun, Peizhen; Sun, Yudi; Jiang, Hongyan; Jia, Ru; Li, Zhiyuan (Frontiers in Psychology, 2019)
The current study investigated the relationship between gratitude, internalizing and externalizing problem behaviors, along with the mediating role of positive and negative coping styles therein. A sample of 589 Chinese adolescents completed the Gratitude Questionnaire (GQ-6), the Simplified Coping Style Questionnaire (SCSQ), the Irritability, Depression and Anxiety Scale (IDAS) and the Aggression Questionnaire (AQ). Results of structural equation modeling showed that 1) the total effects of gratitude on both internalizing and externalizing problem behaviors were all significant; and 2) both positive and negative coping styles mediated the links between gratitude and two types of problem behaviors. Thus, cultivating gratitude and developing adaptive coping style may help adolescents rectify problem behaviors.